Implementasi Pembelajaran Discovery Learning pada Materi Temperatur, Tekanan dan Energi untuk Meningkatkan Pembelajaran Fisika di SMA Kelas X - Pedro Aldriner Sihite; Muhammad Farid; Afrizal Mayub (PendIPA Journal of Science Education, 2019)
ABSTRACT[Implementation Of  Discovery Learning (Dl)  On Temperature, Force And Energy Material To Improve The Physics Learning At Grade X SMA]. This research aimed to describe the improvement of students’ cognitive learning result which was taught by using Discovery Learning (DL) model in teaching temperature, pressure, and energy materials at SMAN 1 Bengkulu Tengah and also to describe the differences of the improvement of students’ cognitive result between high, middle, and low group students. The subject of this research is grade X ipa 1 SMAN 1 Bengkulu Tengah students with total 30 students. This research was a quasi experiment research with one group pretest and posttest design. The data was collected by using test instrument which was multiple choice questions. The data of students’ score at the final test on the last semester became the base of grouping students’ score for high, middle, and low group. The data of pretest and posttest was analyzed descriptively and counted by using gain score which has been normalized and also analyzed by using Anava test. The result of N-gain based on the group which was high group was 0,74; middle group was 0,52; and low group was 0,38. Based on the Anova test which was done to know the differences of students’ cognitive result among the students’ group, it was found Fcount 4,04 > Ftable 3,35 and sig.1,81 ? 4,95. The conclusion of this research was Discovery Learning (DL) model in physics learning for temperature, pressure, and energy materials can improve the students’ cognitive result and there was a significant difference on the improvement of students’ cognitive learning result among high, middle, and low group of students. Keywords: Discovery Learning; Temperature, Pressure and Energy; Cognitive Learning.(Received November 19, 2018; Accepted April 15, 2019; Published June 18, 2019) AbstrakPenelitian ini bertujuan untuk menjelaskan peningkatan hasil belajar kognitif siswa yang diajarkan menggunakan model pembelajaran Discovery Learning (DL)   dalam pembelajaran Temperatur, Tekanan dan Energi  di SMA N 1 Bengkulu Tengah serta menjelaskan perbedaan peningkatan hasil belajar kognitif antara siswa kelompok tinggi, sedang dan rendah. Subjek penelitian ini adalah kelas XIpa1 SMA N 1 Bengkulu Tengah yang berjumlah 30 orang siswa. Jenis penelitian adalah quasi Eksperimen dengan desain one group pretest and posttest design. Data hasil belajar kognitif siswa diperoleh dengan instrumen tes yaitu soal pilihan ganda. Data hasil nilai uijan semester ganjil menjadi dasar pengelompokan siswa ke dalam kelompok tinggi, sedang dan rendah.  Data  hasil belajar kognitif berdasarkan nilai pretest dan posttest dianalisis secara deskriptif dan dihitung dengan menggunakan skor gain yang dinormalisasi serta dianalisis menggunakan uji Anava. Hasil penelitian N-gain berdasarkan kelompok yaitu kelompok tinggi sebesar 0,74; kelompok sedang sebesar 0,52; dan kelompok rendah  sebesar 0,38. Berdasarkan uji anova yang dilakukan untuk mengetahui perbedaan hasil belajar kognitif antar kelompok siswa diperoleh Fhitung 4,04 > Ftabel 3,35 dan nilai sig. 1,81 ? 4,95. Kesimpulan penelitian ini adalah model pembelajaran Discovery Learning (DL)  dalam pembelajaran fisika materi Temperatur, Tekanan dan Energi dapat meningkatkan hasil belajar kognitif siswa dan terdapat perbedaan peningkatan hasil belajar kognitif yang signifikan antara siswa kelompok tinggi, sedang dan rendah.Kata kunci: Discovery Learning; Temperatur, Tekanan dan Energi; Hasil belajar kognitif.